2020
DOI: 10.3389/fimmu.2020.01512
|View full text |Cite
|
Sign up to set email alerts
|

Flattening the COVID-19 Curve With Natural Killer Cell Based Immunotherapies

Abstract: Natural Killer (NK) cells are innate immune responders critical for viral clearance and immunomodulation. Despite their vital role in viral infection, the contribution of NK cells in fighting SARS-CoV-2 has not yet been directly investigated. Insights into pathophysiology and therapeutic opportunities can therefore be inferred from studies assessing NK cell phenotype and function during SARS, MERS, and COVID-19. These studies suggest a reduction in circulating NK cell numbers and/or an exhausted phenotype foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
148
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(157 citation statements)
references
References 259 publications
6
148
0
3
Order By: Relevance
“…Interestingly, we also observed a reduction in CD3 -GzmB + NK cells in diseased patients, indicative of a ~50% depletion of brain NK cells that has been described in the periphery of COVID-19 patients and is implicated in a more severe clinical course of COVID-19 15,16 . Given the profound immune activation in COVID-19 brains, we wondered whether this robust immune activation pattern in the brain stem was linked to tissue destruction and neuronal damage.…”
Section: Highly Multiplexed Imaging Of the Brain Microarchitecture Bysupporting
confidence: 65%
“…Interestingly, we also observed a reduction in CD3 -GzmB + NK cells in diseased patients, indicative of a ~50% depletion of brain NK cells that has been described in the periphery of COVID-19 patients and is implicated in a more severe clinical course of COVID-19 15,16 . Given the profound immune activation in COVID-19 brains, we wondered whether this robust immune activation pattern in the brain stem was linked to tissue destruction and neuronal damage.…”
Section: Highly Multiplexed Imaging Of the Brain Microarchitecture Bysupporting
confidence: 65%
“…Several trials are also investigation the use of oxygen therapy in the early treatment of SARS-CoV-2 infection, as previous studies have shown that this treatment effectively decreases inflammation, reducing IL-12 and TNF-α, and increasing IL10 [ 128 , 129 ]. Numerous trials are investigating the possibility that the Bacille Calmette-GuĂ©rin (BCG) vaccine, used to protect young children against tuberculosis ( Mycobacterium tuberculosis ), may offer heterologous protection against SARS-CoV-2 through trained immunity [ 130 ]. BCG vaccination may lead to epigenetic changes in monocyte and NK cell populations, resulting in an enhanced immune response to subsequent infections, particularly through increased expression of IL-1ÎČ, TNF and IL-6 [ 131 ].…”
Section: Immunological Features Of Covid-19mentioning
confidence: 99%
“…However, what about the therapeutic indication of NK cells in infectious diseases in general and in the lungs particularly? Due to the current COVID-19 pandemic, this question has gained increased interest (108,109), and in addition, most of the papers discussed here that describe an influence of NK cells on the disease course in the airways conclude with the statement that NK cells should be targeted in respiratory infections. But it has clearly been shown that these lymphocytes can have detrimental side effects and cause significant damage to the airways, at least in viral diseases (108,109).…”
Section: Natural Killer Cells As a Therapeutic Option For Airway Infementioning
confidence: 98%
“…Due to the current COVID-19 pandemic, this question has gained increased interest (108,109), and in addition, most of the papers discussed here that describe an influence of NK cells on the disease course in the airways conclude with the statement that NK cells should be targeted in respiratory infections. But it has clearly been shown that these lymphocytes can have detrimental side effects and cause significant damage to the airways, at least in viral diseases (108,109). Available literature does not give clear indications regarding bacterial pathogenesis, but the issue was already discussed in 2012, with the question if NK cells are angels or devils in bacterial infectious diseases (50).…”
Section: Natural Killer Cells As a Therapeutic Option For Airway Infementioning
confidence: 98%